Vibrio cholerae Pathogenic Clones - Salim, Anna (Centers for Disease Control and Prevention, 2005)
We resolved the relationships between 2 pandemic clones of Vibrio cholerae. Using 26 housekeeping genes, we showed that the US Gulf clone, the Australian clone, and 3 El Tor strains isolated before the seventh pandemic were related to the seventh pandemic clone. The sixth pandemic clone was well separated from them.